Treatment of lateral periodontal cyst with guided tissue regeneration - KURU, LEYLA; AĞRALI, ÖMER BİRKAN (My University, 2014)
ABSTRACT Lateral periodontal cyst (LPC), originated from epithelial rests in the periodontal ligament, is a noninflammatory cyst on the lateral surface of the root of a vital tooth. LPC is generally asymptomatic and presents a round or oval uniform lucency with well-defined borders radiographically. In this case report, clinical, histological and radiographical findings and periodontal treatment of 32-year-old female patient, who was referred to Department of Periodontology Clinic of Faculty of Dentistry, Marmara University with a painless hyperplastic lesion on the distobuccal site of the tooth number 12, were presented. The tooth number 12 was vital and a well-defined round radiolucent area with corticated borders was determined radiographically. Preliminary diagnosis was LPC based on clinical and radiographical findings. Mechanical periodontal treatment consisted of oral hygiene instructions, scaling and root planing was applied and flap operation was performed to gain access to the lesion. Following enucleation of the lesion, alveolar bone destruction shaped as a tunnel from labial to palatinal site was observed. The bone cavity was grafted with bovine-derived xenograft, followed by placement of a resorbable collagen membrane. Tissues removed from of the lesion were examined histologically. Hematoxylen-eosin stained sections showed vasculature granulomatous structure underlying squamous epithelium, and destructed bone spaces, all of which were consisted with LPC. Acceptable clinical healing was achieved at 6 months follow-up period. Satisfactory clinical and radiographical outcome can be achieved in the treatment of LPC using regenerative periodontal approach.